Marsupella subemarginata (Gymnomitriaceae, Marchantiophyta) Newly Found in the Carpathians in the Polish and Slovak Tatras - Piotr Górski (Acta Societatis Botanicorum Poloniae, 2022)
Marsupella subemarginata Bakalin Fedosov is a semi-cryptic Eurasian species. Recently, it has been found in the Far East (Kamchatka and Japan) and Swiss Alps, as well as the Giant Mountains (Sudetes, Czech Republic). The plant was also observed in the Carpathians for the first time. A revision of the herbarium collections of M. emarginata (Ehrh.) Dumort. consisting of 102 specimens from the Polish and Slovak Tatra Mountains revealed the occurrence of M. subemarginata at 24 localities, eight of which were in the Polish Tatras. Most of the localities of this species were concentrated in the High Tatras, and only four sites were discovered in the Western Tatras. Marsupella subemarginata has been briefly characterized morphologically and illustrated. The habitat requirements of the species have been described in detail, and the floristic composition of its phytocoenoses has been shown in a phytosociological table consisting of 10 relev’s. Marsupella subemarginata is a valuable addition to the liverwort flora of Poland and Slovakia, which currently consist of 241 and 232 species, respectively. Currently, the liverwort flora of the Tatras comprises 195 species, including 185 species in Poland and 186 species in Slovakia.